Evidence in chronic fatigue syndrome for severity‐dependent upregulation of prefrontal myelination that is independent of anxiety and depression. (March 2015) - Barnden, Leighton R.; Crouch, Benjamin; Kwiatek, Richard; Burnet, Richard; Del Fante, Peter
<x xml:space="preserve">Abstract</x> White matter (WM) involvement in chronic fatigue syndrome (CFS) was assessed using voxel‐based regressions of brain MRI against CFS severity scores and CFS duration in 25 subjects with CFS and 25 normal controls (NCs). As well as voxel‐based morphometry, a novel voxel‐based quantitative analysis of T1‐ and T2‐weighted spin‐echo (T1w and T2w) MRI signal level was performed. Severity scores included the Bell CFS disability scale and scores based on the 10 most common CFS symptoms. Hospital Anxiety and Depression Scale (HADS) depression and anxiety scores were included as nuisance covariates. By relaxing the threshold for cluster formation, we showed that the T1w signal is elevated with increasing CFS severity in the ventrolateral thalamus, internal capsule and prefrontal WM. Earlier reports of WM volume losses and neuroinflammation in the midbrain, together with the upregulated prefrontal myelination suggested here, are consistent with the midbrain changes being associated with impaired nerve conduction which stimulates a plastic response on the cortical side of the thalamic relay in the same circuits. The T2w signal versus CFS duration and comparison of T2w signal in the CFS group with the NC group revealed changes in the right middle temporal lobe WM, where impaired communication can affect cognitive function. Adjustment for depression markedly strengthened cluster statistics and increased cluster size in both T1w severity regressions, but adjustment for anxiety less so. Thus, depression and anxiety are statistical confounders here, meaning that they contribute variance to the T1w signal in prefrontal WM but this does not correlate with the co‐located variance from CFS severity. MRI regressions with depression itself only detected associations with WM volume, also located in prefrontal WM. We propose that impaired reciprocal brain–body and brain–brain communication through the midbrain provokes peripheral and central responses which contribute to CFS symptoms. Although anxiety, depression and CFS may share biological features, the present evidence indicates that CFS is a distinct disorder. © 2015 The Authors. NMR in Biomedicine published by John Wiley & Sons, Ltd.